Knowledge, Attitude and practices of parents about child oral health in Chennai-A Questionnaire based study - P. , Kuzhalvaimozhi; Jeevanandan, Ganesh; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Mothers’ dental knowledge has a vital role on children’s dental health. Oral health is an integral part of general health in infants and children and impacts the quality of life and health outcome. A common misconception that milk teeth of children will exfoliate and there is a less need to seek expert dental advice may lead to various dental problems. Parents knowledge affects their behavior towards maintaining oral hygiene practice. However, only a weak relation exists between knowledge and behavior. There are reports that there is an association between increased knowledge and better oral health. Aim of the study is to analyze the knowledge, attitude and practices of parents about child oral health in Chennai.